PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DAN APLIKASINYA DALAM PEMBELAJARAN PAI DI SEKOLAH - Zaini Gunawan; Ainur Rahmah (PEDAGOGIK : JURNAL PENDIDIKAN, 2019)
This paper aims to describe the development of PAI learning through a contextual teaching and learning approach. Effective learning is learning that is able to create an atmosphere that is fun and not boring, provides experience and the real world in learning and uses a variety of learning resources. This research uses a qualitative approach to the type of library research. The data analysis technique uses content analysis. The results of the study show that the contextual teaching and learning approach is very suitable to be applied in Islamic Religious Education learning in schools, because this approach applies the students' development, skills, experience and contextual understanding of the relationship of subjects with the real world in everyday life. In practice, Islamic Religious Education teachers must pay attention to every component in the contextual teaching and learning approach.